2002
DOI: 10.1046/j.1469-8137.2002.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal taxa differing in response to nitrogen deposition also differ in pure culture organic nitrogen use and natural abundance of nitrogen isotopes

Abstract: Summary• Ectomycorrhizal fungal species vary in their response to nitrogen (N) availability and ability to use organic N. We hypothesized that taxa dominant at sites with high soil inorganic N would be less likely to use organic N than taxa dominant at low soil inorganic N. We also asked whether these taxa differed in natural abundance of N isotopes.• Pure culture N use for taxa from an N deposition gradient in Alaska was examined and N isotopes of sporocarps, soils and foliage collected over this gradient wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
207
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 69 publications
13
207
2
1
Order By: Relevance
“…In this way, it will be possible to obtain a more complete ectomycorrhizal fungi to use organic food sources (Read & Perez-Moreno, 2003). Ectomycorrhizal fungi have the ability to degrade proteins; this ability varies considerably among the different species (Abuzinadah & Read, 1986;Finlay et al, 1992;Lilleskov et al, 2002;Nygren, 2008). The isolates examined in this study were able to use organic nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, it will be possible to obtain a more complete ectomycorrhizal fungi to use organic food sources (Read & Perez-Moreno, 2003). Ectomycorrhizal fungi have the ability to degrade proteins; this ability varies considerably among the different species (Abuzinadah & Read, 1986;Finlay et al, 1992;Lilleskov et al, 2002;Nygren, 2008). The isolates examined in this study were able to use organic nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
“…In forest soil, nitrogen is largely in the form of organic compounds, which are unavailable for direct plant uptake. Therefore, organic nitrogen can not be utilized without transformation and translocation by neither ectomycorrhizal fungi nor other soil organisms (Keller, 1996;Lilleskov et al, 2002). Since ectomycorrhizal fungi are a component of conifer forests, which are characterised by low mineral nitrogen content, it is considered that their ability to use protein nitrogen is widespread (Finlay et al, 1992;Lilleskov et al, 2002;Nygren, 2008,).…”
Section: Effect Of Temperature Ph Carbon and Nitrogen Sources On Mymentioning
confidence: 99%
“…Other studies have confirmed that sporophores of ectomycorrhizal fungi are often more enriched in 15 N than sporophores of saprotrophic fungi, whereas sporophores of saprotrophic fungi are almost always enriched in 13 C compared to sporophores of ectomycorrhizal fungi (Hobbie et al, 1999;2002;Kohzu et al, 1999;2000;Taylor et al, 2003;Trudell et al, 2004). Lilleskov et al (2002) demonstrated that isotope signatures reflect ecophysiological functions. Ectomycorrhizal fungi that utilise organic sources of nitrogen exhibit higher δ 15 N than ectomycorrhizal species using mineral nitrogen.…”
Section: Introductionmentioning
confidence: 93%
“…Proteins can be used by many although not all ECM fungi as sole nitrogen source Finlay et al 1992;Guidot et al 2005;Hutchison 1990;Keller 1996;Lilleskov et al 2002;Lundeberg 1970;Rangel-Castro et al 2002). Proteins often form protein-phenol complexes with tannins and thus become less easily degradable for microorganisms.…”
Section: Enzymes Of Ecms Possibly Involved In Utilising Organic Boundmentioning
confidence: 99%